Le voyage au centre de l’Europe : l’avant-garde parisienne dans la collection internationale d’art moderne à Łódź - Matylda Taszycka (Les Cahiers de l'École du Louvre)
In the late 1920s, the members of the Polish avant-garde a.r. Group decided to put together a collection to demonstrate the principal trends of modern art present in Europe. Over a few, they managed to bring together several dozen works that now constitute the historical collection of the Muzeum Sztuki of Łódź (Poland). Constituted thanks to the generosity of the authors solicited, local and foreign, this exceptional ensemble is similar to an artist’s collection whose study enables the international relations of the Polish avant-garde in the interwar period to be retraced. The article analyses the strategy of the a.r. Group and examines the vision of the history of modern art that the artists sought to convey through their collection.